2013
DOI: 10.5152/akd.2013.073
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Turkey: Epidemiologic Registry (AFTER) study design

Abstract: Objective: Atrial fibrillation (AF) is an important health problem in Turkey. However, no prospective, multicenter, large trial reflecting national data has been published so far. Therefore, the aim of this study was to follow, analyze and evaluate patients with AF in a large multicenter nation-wide trial. Methods: Two thousand three hundred consecutive patients with AF in their electrocardiogram, reflecting all the population of seven geographical regions of Turkey will be included in the study. The patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 11 publications
4
18
1
Order By: Relevance
“…The first epidemiologic registry about non-valvular AF was started in Turkey with the AFTER study (15). In the AFTER study, it was shown that the TTR level was detected in 41.3% of the patients with AF in Turkey (16).…”
Section: Discussionmentioning
confidence: 99%
“…The first epidemiologic registry about non-valvular AF was started in Turkey with the AFTER study (15). In the AFTER study, it was shown that the TTR level was detected in 41.3% of the patients with AF in Turkey (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are several predictors of PAF, such as hypertension, heart failure, valvular heart disease, and hyperthyroidism (14, 15). In our previous multicenter study, the Atrial Fibrillation Registry in Turkey (AFTER), we found that hypertension was the most common comorbid condition in patients with AF (16, 17). In fact, an increased P wave duration on standard 12-lead ECG indicates the presence of an atrial conduction disorder (18).…”
Section: Discussionmentioning
confidence: 99%
“…They were included in the study in a manner of refl ecting the population of all geographic regions of Turkey [11]. These centers were interviewed and informed about the number of patients that they should admit to the study according to the population of the city.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%